Non-enzymatic protein targeting agents as a promising strategy for cancer treatment - Madison Ambrose; Jeremy Lee; Aleem Syed; Zamal Ahmed; Guang Peng (Frontiers in Drug Discovery)
Increased research attention has been brought to non-enzymatic protein targeting agents as a new and effective strategy for advancing cancer treatment. To discover this class of new anticancer drugs, two molecular approaches targeting the non-enzymatic activities of proteins have shown promising experimental, preclinical, and clinical results. In the first approach, selective agents known as PROteolysis-TArgeting Chimeras (PROTACs) employ innate endogenous protein degradation machinery in cells to proteolyze the targeted protein. The combination of the highly selective PROTACs and exploitation of cellular protein degradation pathways provides the opportunity to treat diseases that were previously deemed incurable due to lack of enzymatic activities of the targeted proteins. The second approach targets protein-protein interactions (PPIs) as an alternative non-enzymatic route that alters the functional activities of protein complexes and thus significantly influence cancer cell fitness and survival. To efficiently identify potential chemical leads for these approaches, high-throughput screening (HTS) has been extremely valuable due to its ability to quickly screen large libraries of compounds. In this review paper, we will provide an overview of developing anti-cancer agents targeting non-enzymatic activities of proteins and the potential clinical impact of this new class of inhibitors.